Analisis Kesejahteraan Petani Tambak Udang Vaname Desa Sialang Buah Kecamatan Teluk Mengkudu Kabupaten Serdang Berdagai dalam Perspektif Ekonomi Islam - Risfa Dwi Andini; Sugianto Sugianto; Khairina Tambunan (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Welfare can be measured and understood through various economic and social indicators. General well-being refers to the condition in which a society generally feels happy, healthy, and has its basic needs met, such as food, shelter, education, and decent work. One welfare that has attracted attention is the welfare of coastal areas where the majority of coastal residents work as fishermen. There are several residents who are trying out the shrimp farming business. The type of shrimp they take is vanamei shrimp. Therefore, the aim of this research is to determine the welfare status of shrimp farmers who follow the guidelines of the Islamic economic system. A qualitative approach was used in this research. To carry out a research approach, observations and interviews were carried out. Based on the results of observations, the expenditure of shrimp pond farmers varies from the profits earned by pond farmers, which is very sufficient to meet all needs, both in terms of education, health and adequate consumption. The monthly profit they get from white shrimp pond farmers is IDR 11,631,666, compared to the Serdang Berdagai Regency Minimum Wage (UMK) of IDR 3,111,250 and the average expenditure of shrimp pond farmers is IDR 9,000,000/month. With this profit, all the needs of pond farmers are fulfilled and well met, so that shrimp pond farmers are at a very good level of welfare.